If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(a + -10) = 3 Reorder the terms: 3(-10 + a) = 3 (-10 * 3 + a * 3) = 3 (-30 + 3a) = 3 Solving -30 + 3a = 3 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 30 + 3a = 3 + 30 Combine like terms: -30 + 30 = 0 0 + 3a = 3 + 30 3a = 3 + 30 Combine like terms: 3 + 30 = 33 3a = 33 Divide each side by '3'. a = 11 Simplifying a = 11
| 4cosx+2sinx=3 | | (q-6)*3=9 | | (q-6)*4=9 | | 6(3s+8)=156 | | 5(a-3)=65 | | 8x^2-2xy*-3y^2=0 | | 3+91x=39x+11 | | 2x^2=3x+12 | | 3a^2+a-10=0 | | 24-6x=12-8x | | (A-3)(3a-1)= | | -3.6r-4.5r=-6.48 | | 5.5+2.2n-4.789n=-3.3026 | | -3.5x+3.3x=0.86 | | 2(3x-4)+3(2x+2)=142 | | (x+5)(y-3)=0 | | 4x+11=-43-5x | | -4.3r-2.2r=13 | | (2z+6)(z-2)= | | m+2.6+0.26=3.76 | | xy+5y-3x=15 | | 4.79n+3.9n=-13.035 | | X-0.80X=5159 | | 20x+55y=92.65 | | 5x+x-10=20-6x | | x(2)+8=24 | | 0.837x-2.1+3.6x=17.498229 | | 3x-22=2-5x | | 3log[5](x*x-17)=log[5](x+3) | | 8-w+6=9w-2 | | Y-14=3y+4 | | 18x^3-14x^2+6x= |